The effects of tax clienteles on disclosure: Evidence from the municipal bond market - Chen, Novia; Hutchens, Michelle; Xia, Junwei (Journal of Accounting and Economics, 2026)
The municipal bond market has long been criticized for its lack of disclosure, which prior research often attributes to weak regulatory oversight. We offer another explanation: tax clienteles. Most municipal bonds are tax-exempt, and thus primarily attract high-tax retail investors, who may lack the incentive or ability to demand or monitor disclosures. In contrast, taxable bonds attract a broader investor base, including institutional investors who can demand disclosure. We find that issuers provide more continuing disclosures in years with taxable bonds outstanding relative to years without. Issuers also increase disclosures after issuing their first taxable bond and decrease disclosures after calling their last taxable bond. Exploiting a tax law change, we find that disclosures increase following plausibly exogenous increases in taxable bond issuances. Our results suggest that the tax clienteles for municipal bonds affect issuers’ disclosure practices and can inform those concerned with disclosure noncompliance in the municipal bond market.